2013
DOI: 10.1016/j.jcmg.2012.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Fibrosis in Hypertrophic Cardiomyopathy

Abstract: CMR-LGE measured at 4 SD and 5 SD yields the closest approximation to the extent of total fibrosis measured by the histopathological standard of reference. These findings have implications for future investigations of CMR-LGE and its association with important clinical endpoints in HCM, including sudden cardiac death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0
4

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 189 publications
(60 citation statements)
references
References 30 publications
2
54
0
4
Order By: Relevance
“…Depending on different clinical and imaging applications, quantification of myocardial fibrosis in LGE CMR images has been performed with SI thresholding that differs among studies [3942]. We presented a comparative assessment for the amount of fibrosis using various levels of threshold and showed all thresholds achieved a high accuracy separating the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on different clinical and imaging applications, quantification of myocardial fibrosis in LGE CMR images has been performed with SI thresholding that differs among studies [3942]. We presented a comparative assessment for the amount of fibrosis using various levels of threshold and showed all thresholds achieved a high accuracy separating the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, LGE has the unique ability to identify areas of fibrosis. 23,24 Scarce data exist on the genotype-phenotype association in patients with HCM as assessed by CMR. 25 We sought to compare CMR phenotype between patients harboring mutations in the 2 most common genes, MYH7 and MYBPC3.…”
Section: Weissler-snir Et Al Phenotypic-genotypic Correlation By Cmr mentioning
confidence: 99%
“…A retrospective study of 1293 patients demonstrated that LGE>15% of LV mass was associated with a 2-fold increase in SCD risk (8), suggesting that the amount of LGE rather than just its presence may be an important risk marker. LGE identifies replacement and interstitial fibrosis(9), but post-mortem analysis indicates that diffuse fibrosis is also present in other regions not identified by LGE. Recent advances in T1 mapping with CMR (10) have enabled validation of diffuse interstitial fibrosis measurements in HCM (11) and demonstration of increases, even in genotype (+), phenotype (−) patients(12).…”
Section: Introductionmentioning
confidence: 99%